Hydrolysis products from sockeye (Oncorhynchus nerka L.) heads from the Kamchatka Peninsula produced by different methods: biological value - Vladimir V. Volkov; Olga Ya. Mezenova; Joerg-Thomas Moersel; Sascha Kuehn; Thomas Grimm; Axel Hoehling; Sergei A. Barabanov; Kirill S. Volkov (Foods and Raw Materials, 2021)
Introduction. Sockeye salmon (Oncorhynchus nerka L.) is a valuable Pacific salmon. Sockeye heads are a significant share in processing sockeye salmon. Traditionally, fish by-products are used to make fishmeal. However, due to the high content of collagen proteins and fat in sockeye salmon heads, it is difficult to produce fishmeal from this raw material. Controlled enzymatic or combined hydrolysis allows protein, fat, and minerals to be extracted to supply the market with higher value products with desirable features. This research was aimed to analyze the chemical composition and biological value of hydrolysis products obtained from sockeye heads. Study objects and methods. We investigated hydrolysis products of sockeye salmon heads, namely protein hydrolysates, fat and sludge. Thermal hydrolysis and enzymatic-thermal hydrolysis were used for the tests. Thermal hydrolysis was realized in reactor. For enzymatic-thermal hydrolysis, the raw material was pre-treated by proteolytic enzyme Alcalase. The hydrolysates obtained were investigated. Chemical composition was determined in accordance with State Standard 7636-85. HPLC was used for molecular weight and amino acid analysis. Gas chromatography was used for fatty acid analysis. Biological value of proteins was determined by the balance of the amino acid composition comparing it with the “ideal protein model”. Results and discussion. Thermal hydrolysis resulted in the production of protein hydrolysate powder with protein content of 92.0% dry matter and a protein recovery rate of 39.6%. Combined hydrolysis resulted in the production of protein hydrolysate powder with protein content of 92.6% and a protein recovery rate of 83%. All protein hydrolysates contained all essential amino acids. The biological value of protein hydrolysate obtained by thermal and combined hydrolysis was 80.1 and 82.8%, respectively. Conclusion. Hydrolysed products obtained by thermal and enzymatic-thermal hydrolysis had a valuable chemical composition and could be recommended for food and ...